2018
DOI: 10.1182/blood-2018-01-821629
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2b study of 2 dosing regimens of quizartinib monotherapy in FLT3-ITD–mutated, relapsed or refractory AML

Abstract: This randomized, open-label, phase 2b study (NCT01565668) evaluated the efficacy and safety of 2 dosing regimens of quizartinib monotherapy in patients with relapsed/refractory (R/R) -internal tandem duplication (ITD)-mutated acute myeloid leukemia (AML) who previously underwent transplant or 1 second-line salvage therapy. Patients (N = 76) were randomly assigned to 30- or 60-mg/day doses (escalations to 60 or 90 mg/day, respectively, permitted for lack/loss of response) of single-agent oral quizartinib dihydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
118
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 131 publications
(123 citation statements)
references
References 28 publications
3
118
0
1
Order By: Relevance
“…Although there were no clinically relevant QT prolongations with concomitant administration of ketoconazole or fluconazole with a single 30-mg dose of quizartinib in the current study, clinically relevant and dose-dependent QT prolongations have been observed following repeat daily dosing of quizartinib in previous clinical studies in patients with AML. [5][6][7]21 The increased exposure to quizartinib with ketoconazole supports reducing quizartinib doses in patients receiving a strong CYP3A inhibitor. Based on the fluconazole arm data, no dose reduction is needed when quizartinib is coadministered with a moderate or weak CYP3A inhibitor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there were no clinically relevant QT prolongations with concomitant administration of ketoconazole or fluconazole with a single 30-mg dose of quizartinib in the current study, clinically relevant and dose-dependent QT prolongations have been observed following repeat daily dosing of quizartinib in previous clinical studies in patients with AML. [5][6][7]21 The increased exposure to quizartinib with ketoconazole supports reducing quizartinib doses in patients receiving a strong CYP3A inhibitor. Based on the fluconazole arm data, no dose reduction is needed when quizartinib is coadministered with a moderate or weak CYP3A inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples for measurement of plasma quizartinib and AC886 concentrations were collected from all subjects before quizartinib dosing on Day 8 and at 0.25, 0.5, 1, 2, 3,4,5,6,8,12,24,36,48,72,96,120,144,168,192,216,288,360,432 to 98.5%. For quizartinib at the upper limit of quantitation, precision FIGURE 1 Study design.…”
Section: Sample Collection and Analytic Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…[160][161][162] Nevertheless, recent studies indicate that AML patients with NPM1 mutation and low FLT3-ITD allelic ratio may have a more favorable prognosis and should therefore not routinely be assigned to allo-SCT. 103,163,164 In contrast, an ITD insertion site in the TKD1 remained an unfavorable prognostic factor regardless of the applied therapy. 102 Currently, midostaurin (Rydapt ® , Novartis Pharmaceuticals, Inc.)…”
Section: Itd627e Induced Transformation Of Hematopoietic 32d Cells Anmentioning
confidence: 95%
“…Currently, various other, more selective FLT3 inhibitors, such as quizartinib, 164,165 crenolanib, 166 and gilteritinib, 167…”
Section: Itd627e Induced Transformation Of Hematopoietic 32d Cells Anmentioning
confidence: 99%